Kontruksi Lingkungan Hidup Pada Jurnalisme Warga Di Media Sosial Tiktok @Pandawara Group - Wulandari, Tri Andiyani; Muhaemin, Enjang; Darsono, Dono (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2024)
This study aims to determine the meaning of denotation, connotation meaning, and myth with reference to (a) how the video content of citizen journalism on environmental issues on social media tiktok @Pandawara Group is seen from the denotation aspect (b) seen connotation meaning (c) and seen the meaning of myth. The method used in this research is a qualitative method using analytical techniques. The theory used in this research is the Roland Barthes semiotics model. This study will analyze how Citizen Journalism on environmental issues on Tiktok social media on the @Pandawara Group account. The results of the research on Tiktok @Pandawara Group content have a denotation meaning, namely that the Pandawara Group always invites the community and related elements to carry out every joint activity and proves that voicing environmental issues can be through social media. The connotation meaning is conveyed through gestures and symbols, attitudes and expressions shown. The mythical meaning is conveyed through the symbol of gotong royong which is identical to Indonesian society.